Tiburones fabulosos - Simon, Seymour; Bell, Elizabeth S. (San Francisco : Chronicle Books, 2006)
An introduction to the physical characteristics and behavior of various kinds of sharks.
"Nivel 1"--Cover.
"iCon 4 Tarjetas para coleccionar!"--Cover.
Accelerated Reader
Keywords: Sharks -- Juvenile literature; Tiburones -- Literatura juvenil